Integrin αDβ2 (CD11d/CD18) Modulates Leukocyte Accumulation, Pathogen Clearance, and Pyroptosis in Experimental Salmonella Typhimurium Infection - Nascimento, Danielle de Oliveira; Vieira-de-Abreu, Adriana; Arcanjo, Angélica F.; Bozza, Patricia Torres; Zimmerman, Guy A.; Castro-Faria-Neto, Hugo Caire (Frontiers in Immunology, 2018)
β2 integrins (Coxon, Rieu et al. 1996) are critical in host defense responses to invading pathogens and inflammation. Previously, we reported that genetic deficiency of integrin αDβ2 in mice altered outcomes in experimental systemic infections including accelerated mortality in animals infected with Salmonella enterica serovar Typhimurium (Broz, Newton et al.). Here we show that deficiency of αDβ2 results in impaired accumulation of leukocytes in response to peritoneal infection by S. Typhimurium, impaired pathogen clearance in vivo, defective bacterial elimination by cultured peritoneal macrophages, and enhanced pyroptosis, a unique macrophage cell death process triggered by Salmonella. Salmonella-infected animals deficient in αDβ2 had increased levels of peritoneal cytokines in addition to other markers of pyroptosis, which may contribute to inflammatory injury and increased mortality in the context of impaired bacterial killing. These observations indicate important contributions of leukocyte integrins to the host response in experimental Salmonella infection and reveal previously-unrecognized activities of αDβ2 in bacterial infection.